Avaliação da sustentabilidade na gestão de resíduos sólidos urbanos: estudo de caso envolvendo segmentos sociais do município de Feira de Santana, Bahia - Santos, Aline Santana dos (2015)
The research aimed to evaluate the sustainability of Municipal Solid Waste Management in the city of Feira de Santana, Bahia, by applying the matrix of sustainability indicators proposed by Santiago and Dias (2012). The evaluation was preceded by literature review in public databases and academic literature on the economic, social, cultural, environmental situation, policy and solid waste management in the municipality. Thus, aiming to add value to research and enhancing the systemic view, were introduced information on the understanding of 44 social representatives, residents and collectors of recyclable materials on municipal solid waste management, through a questionnaire. In addition, field observations were carried out in 22 of the 44 districts of the municipal headquarters and in eight districts. The array of indicators used is composed of six dimensions of sustainability, key questions and 42 indicators of which five are indicators of the political dimension, four technological, four in the economic / financial dimension, thirteen environmental / ecological dimension, ten dimension of knowledge (Environmental Education and Social Mobilization) and six in the dimension of social inclusion. The matrix also presents three descriptors for each indicator totaling 126, with space for setting of bookmark note that varies from 0 to 5. After application of the matrix, the level of sustainability was 4.1, corresponding to a low- sustainability, and the financial and social inclusion the most unsustainable dimensions. The results found convenes public managers for emergency decision making, such as the development of solid waste management plan, as required by National Policy on Solid Waste and draws attention to the importance of popular participation in the Municipal Solid Waste Management. Against the backdrop, recommendations for sustainable management were proposed.